1997
DOI: 10.1002/bbpc.19971010811
|View full text |Cite
|
Sign up to set email alerts
|

Complexing ability of monensin anion for alkali metal cations in binary mixtures of dipolar aprotic solvents

Abstract: Cyclic voltammetric studies have been carried out on monensin anion complexes with the alkali metal cations in binary mixtures of dimethylsulfoxide with acetonitrile, acetone and hexamethylphosphoric triamide. respectively. The log Ks values obtained for the complexity constants can be well described by empirical relation log Ks = αDN + β, where DN stands for the effective donor number of a given solvent mixture and α and β mark the regression coefficients. This result is in agreement with the predominant role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Due to the high affinity of monensin to complex alkaline metal ions, it is known for a very long time to be a monovalent polyether ionophore (Lutz et al 1971;Briggs and Hinton 1978;Duax et al 1980;Garcla-Rosas et al 1983;Cox et al 1984;Walba et al 1986;Pangborn et al 1987;Rzeszotarska et al 1994;Wagner-Czauderna et al 1997;Paz et al 2003;Huczynski et al 2007aHuczynski et al , b, c, 2008aYildirim et al 2007). From the 1990s up to the present several research groups have drawn attention to the possible complexation of monensin with divalent metal ions (Hebrant et al 1992;Mimouni et al 1994;Dassie and Baruzzi 2002;Hamidinia et al 2002;Huczynski et al 2006aHuczynski et al , b, c, d, 2007aHuczynski et al , b, c, 2008a.…”
Section: Introductionmentioning
confidence: 95%
“…Due to the high affinity of monensin to complex alkaline metal ions, it is known for a very long time to be a monovalent polyether ionophore (Lutz et al 1971;Briggs and Hinton 1978;Duax et al 1980;Garcla-Rosas et al 1983;Cox et al 1984;Walba et al 1986;Pangborn et al 1987;Rzeszotarska et al 1994;Wagner-Czauderna et al 1997;Paz et al 2003;Huczynski et al 2007aHuczynski et al , b, c, 2008aYildirim et al 2007). From the 1990s up to the present several research groups have drawn attention to the possible complexation of monensin with divalent metal ions (Hebrant et al 1992;Mimouni et al 1994;Dassie and Baruzzi 2002;Hamidinia et al 2002;Huczynski et al 2006aHuczynski et al , b, c, d, 2007aHuczynski et al , b, c, 2008a.…”
Section: Introductionmentioning
confidence: 95%
“…An extensive study on affinity of monensin A to bind monovalent metal cations was performed in protic and dipolar aprotic solvents, in heterogeneous systems (water-organic phase) as well as in model biomembranes. [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] Experimental data (cyclovoltammetry, microcalorimetry, potentiometry) [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] revealed that monensinate complexes of IA cations are very stable with sharp stability maximum for sodium complex [Mon À Na + ]. The observed selectivity was explained in terms of cavitycationsize dependence and negative charge of ligand anion, introducing direct electrostatic stabilization.…”
Section: Introductionmentioning
confidence: 99%